Method for synthesizing lithium nickel manganese oxide positive electrode material through rapid Joule thermal shock

Through the rapid scorching ears heat shock technology, the problem of time consumption and energy consumption of lithium nickel manganate material in traditional methods has been solved, and efficient and accurate regulation and control are achieved, and nickel manganate positive materials with excellent electrochemical properties are prepared.

CN119349660AInactive Publication Date: 2025-01-24HANGZHOU DIANZI UNIV +1

Patent Information

Application Number
CN202411908770.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When traditional methods regulate the number of oxygen vacancies, Mn3+ content and Ni/Mn disorder in lithium nickel manganese oxide positive electrode materials in lithium-ion batteries, it consumes time and energy and is difficult to achieve precise regulation, which hinders in-depth research on the electrochemical properties of the materials.

Method used

Rapid Joule thermal shock (JTS) technology is used to achieve rapid calcination of lithium nickel manganese oxide through the Joule heating effect of the conductive substrate, shorten the calcination time to several minutes, and finely adjust the number of oxygen vacancies, Mn3+ content and structural disorder.

Benefits of technology

Efficient and precise control was achieved to prepare lithium nickel manganese oxide cathode material with excellent electrochemical properties, shorten the size of the material particles, and improve the charge and discharge speed and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349660A_ABST
    Figure CN119349660A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing a lithium nickel manganese oxide positive electrode material through rapid Joule thermal shock. The precursor is loaded on a conductive substrate for Joule thermal shock treatment, so that not only can rapid synthesis within several minutes be realized, but also the product has more oxygen vacancy defects due to the characteristic of rapid heating and cooling of Joule heat, and the number of the oxygen vacancy defects can be further changed by changing the Joule thermal shock treatment time; therefore, the Mn < 3 + > content and the disorder degree of the material structure are influenced, and the optimization of the electrochemical performance is realized. According to the invention, efficient and fine regulation and control of oxygen vacancy number, Mn < 3 + > content and structure disorder degree in the LiNi0. 5Mn1. 5O4 material can be realized, and the high-performance LiNi0. 5Mn1. 5O4 material with the capacity retention rate up to 90.8% after 500 cycles under 1C multiplying power and the capacity of 75mAh / g under 5C multiplying power can be synthesized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery material production, and in particular to a method for rapidly synthesizing a nickel manganese oxide positive electrode material using Joule thermal shock. Background Art

[0002] At present, the power density and energy density of lithium-ion batteries still cannot meet the needs of industrial development. The development of lithium-ion batteries with high power density and high energy density has become a research focus. Currently, the industrialized positive electrode materials mainly include lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, and ternary materials. Lithium cobalt oxide is suitable for small batteries, but its disadvantage is that the actual capacity is relatively low; lithium iron phosphate has low cost, high safety performance, and long cycle life, but its voltage is lower than that of general positive electrode materials, resulting in low energy density; Mn in lithium manganese oxide 3+ It will trigger the Jan-Taylor effect, resulting in poor cycle performance and serious high-temperature capacity decay; the Co element in the ternary material is toxic and has a high cost.

[0003] Spinel nickel lithium manganese oxide (LiNi 0.5 Mn 1.5 O4, LNMO) is an excellent cathode material because of its low cost, high operating voltage (4.7 V), excellent lithium ion mobility and stable three-dimensional conductive channel.

[0004] Lithium nickel manganese oxide exhibits two different crystal arrangements: ordered structure and disordered structure. 4332 In the ordered configuration of the space group, nickel (Ni) and manganese (Mn) ions occupy the 4a and 12d octahedral positions, respectively, and the oxidation state is Ni 2+ and Mn 4+ In contrast, in the disordered structure, Ni / Mn ions are randomly dispersed within the 16d octahedral sites, with Mn mainly in the Mn 4+ , accompanied by a small amount of Mn 3+ Existence, Mn 3+ It is electrochemically active and has a small platform at around 4V. The formation of the disordered phase is due to the release of oxygen during the high-temperature calcination of the LNMO material and the incomplete recombination with oxygen during the cooling process, resulting in oxygen vacancies in the material. When oxygen is lost, Mn 4+ The ion is reduced to Mn due to its electrochemical neutrality. 3+ A large number of studies have shown that the electrochemical performance of LNMO is closely related to the number of oxygen vacancies, Mn 3+ There is a close relationship between the content and the degree of disorder of Ni / Mn. When there are too many oxygen vacancies: 1. 3 + Too much leads to the generation of more Mn after disproportionation reaction 2+1. The surface layer of LNMO is reconstructed to form a rock salt structure and a defective spinel structure layer, which leads to increased surface resistance and capacity loss. 2. When the structure is disordered, the stable chemical bonds between atoms are disrupted, and the whole is in a high energy state. Too much disorder will cause the structure to be too unstable and difficult to withstand long-term lithium ion deintercalation. When there are too few oxygen vacancies: 1. There is almost no Mn 3+ ions, and the appropriate content of Mn 3+ It will promote electron hopping and improve conductivity, so the conductivity of completely long-range ordered materials is worse. 2. The structure is almost completely long-range ordered, the lithium ion diffusion channel is fixed, and the lithium ion diffusion channel is small, which is not conducive to lithium ion diffusion. Therefore, it is necessary to accurately and reasonably control the oxygen vacancy concentration, Mn 3+ The content and degree of Ni / Mn disorder are the key strategies for synthesizing high-performance LNMO materials.

[0005] Although the relationship between the internal defect-related mechanism and electrochemical performance of LNMO cathode materials has gradually become a prominent research focus, the shortcomings of traditional processing methods have become increasingly apparent. Most researchers use traditional muffle furnaces and tube furnaces (TF) to adjust the cooling rate, calcination temperature and duration, or add annealing procedures to make adjustments, but the whole process is time-consuming and energy-consuming, and these methods often take more than 10 hours to process, making it difficult to accurately control the number of oxygen vacancies, Mn in a narrow range. 3+ With increasing Ni / Mn content, the degree of Ni / Mn disorder becomes extremely challenging, thus hindering in-depth investigations of the underlying defect-related mechanisms. Therefore, the development of innovative synthesis and defect-modulation techniques is urgently needed. Summary of the invention

[0006] In order to solve the difficulties in existing control technologies, the inventors have explored a method for controlling the oxygen vacancy defects of lithium nickel manganese oxide positive electrode materials through rapid Joule thermal shock (JTS). The entire process time is shortened to only a few minutes, which is a way to overcome the problems of long time and high energy consumption, greatly reduce the control cost, and achieve efficient and precise control of the number of oxygen vacancies in lithium nickel manganese oxide, Mn 3+ The new method is to measure the content and the degree of Ni / Mn disorder, and the lithium nickel manganese oxide material prepared by this method has smaller particles than the lithium nickel manganese oxide material prepared by the traditional method, and finally a lithium nickel manganese oxide positive electrode material with excellent electrochemical properties is synthesized.

[0007] The purpose of the present invention is achieved through the following technical solutions: A method for rapidly synthesizing a nickel-manganese-oxide lithium positive electrode material by Joule thermal shock comprises the following steps: Step 1: weighing raw materials according to the stoichiometric ratio of the lithium nickel manganese oxide positive electrode material to prepare a lithium nickel manganese oxide precursor; Step 2: obtaining a conductive substrate, and using the conductive substrate to sandwich the lithium nickel manganese oxide precursor to fully transfer heat to the lithium nickel manganese oxide precursor; two conductive and heat conductive components are respectively connected to both ends of the conductive substrate; Obtain a power source. Connect the two poles of the power source to the two conductive and thermal conductive components respectively, and conduct electricity according to the preset power-on time and heating temperature. After the conductive substrate is energized, it generates heat to heat the lithium nickel manganese oxide precursor to obtain a lithium nickel manganese oxide positive electrode material; The heating temperature is adjusted by adjusting the preset voltage and current, and the heating time is adjusted by adjusting the preset power-on time; The power-on process is performed according to the preset power-on time and heating temperature, and specifically includes a pre-calcination process, a formal calcination process and an annealing process in sequence.

[0008] Preferably, step 1 specifically includes the following steps: weighing Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and putting them into a ball mill, adding a certain amount of anhydrous ethanol for wet grinding, and ball milling at a speed of 400 rpm for 4 hours, and placing the mixture after ball milling in a vacuum oven at 120°C for 12 hours to obtain a lithium nickel manganese oxide precursor.

[0009] Preferably, in step 2, the power-on time of the pre-calcination process is 2 minutes, and the temperature is 500°C; the power-on time of the formal calcination process is 4-8 minutes, and the temperature is 800-900°C; the power-on time of the annealing process is 0-2 minutes, and the temperature is 600°C; Preferably, the conductive substrate sandwiches the lithium nickel manganese oxide precursor, specifically comprising the following steps: folding the conductive substrate in half, sandwiching the lithium nickel manganese oxide precursor between the folded conductive substrates; Each of the conductive and heat-conducting components includes two brass clamping parts, which are used to clamp the two ends of the folded conductive substrate respectively, so that the conductive substrate and the brass clamping parts are in full contact to reduce contact resistance and quickly conduct heat; the brass clamping part includes two brass blocks.

[0010] Preferably, the raw material Li2CO3 in step 1 is in excess of 10%, which is to supplement lithium in order to prevent the loss of lithium source during the high-temperature treatment process.

[0011] Preferably, in step 2, the conductive substrate comprises any one of the following materials: stainless steel foil, iron foil, tungsten boat, carbon cloth, carbon paper, and graphite material.

[0012] Preferably, the method of sandwiching the lithium nickel manganese oxide precursor between the folded conductive substrates specifically includes: the two ends of the folded conductive substrate are clamped to form a groove, the precursor is placed therein and evenly spread out, so that the precursor is in close and full contact with the conductive substrate, the precursor is heated evenly, and the heat is quickly conducted.

[0013] Preferably, the power supply in step 2 includes any one of a direct current power supply and an alternating current power supply, and the direct current power supply includes a constant current power supply and a constant voltage power supply.

[0014] Preferably, the lithium nickel manganese oxide positive electrode material is in granular form, and the particle size of the particles is between 100nm and 500nm.

[0015] Preferably, the method further comprises the following steps: assembling the lithium nickel manganese oxide positive electrode material as a battery positive electrode to obtain a battery, adjusting the heating temperature and time of the formal calcination process to adjust the number of oxygen vacancies, thereby adjusting the battery cycle performance; setting the pre-calcination temperature to 500° C. and the heating time to 2 min; setting the annealing temperature to 600° C. and the heating time to 2 min; When the formal calcination temperature is 850℃ and the heating time is 4min, the reversible capacity of the battery is still 106.5mAh / g after 500 cycles, and the capacity retention rate reaches 90.8%. It can still maintain a capacity of 75mAh / g at a 5C rate.

[0016] Compared with the prior art, the present invention has the following advantages: (1) The Joule heat effect of the conductive substrate is used to achieve rapid calcination of lithium nickel manganese oxide, shortening the calcination time from tens of hours in traditional methods to a few minutes using rapid thermal shock technology, greatly reducing time consumption and energy consumption. The folded conductive substrate also allows the material to be fully calcined and heated evenly, ensuring the quality of the target product calcined.

[0017] (2) By adjusting the calcination time, calcination temperature, and adding an annealing process during the rapid thermal shock process, it is possible to quickly synthesize lithium nickel manganese oxide with good crystallinity and finely adjust the number of oxygen vacancies, Mn 3+ The content and degree of structural disorder are optimized to optimize the electrochemical performance. The capacity retention rate of the lithium nickel manganese oxide material rationally regulated by the rapid thermal shock method is as high as 90.8% after 500 cycles at a 1C rate, and it can still maintain 75mAh / g at a 5C rate.

[0018] (3) After rapid thermal shock, the lithium nickel manganese oxide particles have smaller submicron particles, which shortens the distance for lithium ion insertion and extraction, speeds up the charging and discharging speed, and improves the rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1The XRD patterns of samples calcined by the traditional method (denoted as TF-LNMO) and samples calcined by rapid thermal shock are shown; the pre-calcination time of 2min and the annealing time of 2min are fixed, and the formal calcination process time is changed to 4min, 6min, and 8min. The three process temperatures are fixed at 500℃, 600℃, and 850℃, respectively, and are denoted as JTS-LNMO-4min, JTS-LNMO-6min, and JTS-LNMO-8min; Figure 2 Shown is the calcination temperature curve of JTS-LNMO-4min; Figure 3 The SEM images of four samples, TF-LNMO, JTS-LNMO-4min, JTS-LNMO-6min, and JTS-LNMO-8min, are shown. The scale of the first row is 1um, and the scale of the second row is 5um. Figure 4 The X-ray photoelectron spectra of O1s orbitals of four samples, TF-LNMO, JTS-LNMO-4min, JTS-LNMO-6min, and JTS-LNMO-8min, are shown. The peak at 531.9 eV is due to the typical TM-O bond, while the signal at 531.5 eV is usually due to surface oxygen defects. Figure 5 Shown are TF-LNMO, JTS-LNMO-4min, JTS-LNMO-6min, and JTS-LNMO-8min (a) 500 cycles at 1C rate and (b) rate performance diagram. DETAILED DESCRIPTION

[0020] In order to further illustrate the present invention to achieve the predetermined purpose of the invention, the present invention is further described in detail in conjunction with the following specific embodiments.

[0021] The method comprises the following steps: Step 1: Weigh Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and put them into a ball mill, then add a certain amount of anhydrous ethanol for wet grinding, and ball mill at a speed of 400 rpm for 4 hours. Put the mixture after ball milling into a vacuum oven at 120°C for 12 hours to obtain a lithium nickel manganese oxide precursor.

[0022] Step 2: Place the lithium nickel manganese oxide precursor in a folded conductive substrate. The two ends of the folded substrate are clamped by two brass blocks and fixed with screws. The two ends of the brass block are connected to the power supply through wires. After power is turned on, calcination is performed twice. The first pre-calcination is directly cooled to room temperature and then the second formal high-temperature calcination begins. In order to improve the crystallinity, the temperature is not immediately cooled to room temperature after the high-temperature calcination program is completed, but it is cooled to a lower temperature and maintained for a period of time before being cooled to room temperature, which is annealing. The current of the pre-calcination process is set to a power-on time of 2 minutes and a temperature of 500°C; the current of the formal calcination process is set to a power-on time of 4-8 minutes and a temperature of 800-900°C; the current of the annealing process is set to a power-on time of 0-2 minutes and a temperature of 600°C.

[0023] Preferably, the raw material Li2CO3 in step 1 is in excess of 10%, which is to prevent lithium source loss during high temperature treatment. The conductive substrate described in step 2 refers to any one of the following materials, stainless steel foil, iron foil, tungsten boat, carbon cloth, carbon paper, graphite material; the folded conductive substrate described in step 2 refers to folding the substrate foil in half, clamping the two ends with brass to form a groove, placing the precursor in it and spreading it evenly, so that the precursor is in close contact with the substrate in the substrate, and trying to ensure that the material is heated more evenly, which is convenient for rapid heat conduction; the power supply described in step 2 refers to any one of direct current and alternating current power supplies, and the direct current power supply also includes constant current power supply and constant voltage power supply; the power-on calcination described in step 2 mainly utilizes the good conductivity of the conductive substrate. When the current passes through the conductor, Joule heat will be generated to cause the conductor temperature to rise, thereby realizing the function of heating and calcining the material on the conductive substrate.

[0024] In the embodiment, the folded conductive substrate is to fold the substrate with a width of 2 cm and a length of 8.5 cm in half along the wide side to divide the width into two halves. The calcination temperature is uniformly detected using an infrared thermometer. Example

[0025] Step 1: Weigh Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and put them into a ball mill, then add a certain amount of anhydrous ethanol for wet grinding, and ball mill at a speed of 400 rpm for 4 hours. Put the mixture after ball milling into a vacuum oven at 120°C for 12 hours to obtain a lithium nickel manganese oxide precursor.

[0026] Step 2: Place the precursor in a folded conductive substrate and calcine the precursor under air atmosphere, pre-calcining at 500°C for 2 minutes and formal calcining at 850°C for 4 minutes. There is no annealing process. The current is set as: 26A for the pre-calcination process and 44A for the formal calcination process. Example

[0027] Step 1: Weigh Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and put them into a ball mill, then add a certain amount of anhydrous ethanol for wet grinding, and ball mill at a speed of 400 rpm for 4 hours. Put the mixture after ball milling into a vacuum oven at 120°C for 12 hours to obtain a lithium nickel manganese oxide precursor.

[0028] Step 2: Place the precursor in a folded conductive substrate and calcine the precursor under air atmosphere, pre-calcining at 500°C for 2 minutes, formal calcining at 800°C for 4 minutes, and annealing at 600°C for 2 minutes. The current is set as follows: pre-calcination process current 26A, formal calcination process current 40A, annealing process current 27.5A. Example

[0029] Step 1: Weigh Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and put them into a ball mill, then add a certain amount of anhydrous ethanol for wet grinding, and ball mill at a speed of 400 rpm for 4 hours. Put the mixture after ball milling into a vacuum oven at 120°C for 12 hours to obtain a lithium nickel manganese oxide precursor.

[0030] Step 2: Place the precursor in a folded conductive substrate and calcine the precursor under air atmosphere, pre-calcining at 500°C for 2 minutes, formal calcining at 850°C for 4 minutes, annealing at 600°C for 2 minutes, and the current is set as: pre-calcination process current 26A, formal calcination process current 44A, annealing process current 27.5A. Example

[0031] Step 1: Weigh Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and put them into a ball mill, then add a certain amount of anhydrous ethanol for wet grinding, and ball mill at a speed of 400 rpm for 4 hours. Put the mixture after ball milling into a vacuum oven at 120°C for 12 hours to obtain a lithium nickel manganese oxide precursor.

[0032] Step 2: Place the precursor in a folded conductive substrate and calcine the precursor under air atmosphere, pre-calcining at 500°C for 2 minutes, formal calcining at 900°C for 4 minutes, annealing at 600°C for 2 minutes, and the current is set as: pre-calcination process current 26A, formal calcination process current 48A, annealing process current 27.5A. Example

[0033] Step 1: Weigh Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and put them into a ball mill, then add a certain amount of anhydrous ethanol for wet grinding, and ball mill at a speed of 400 rpm for 4 hours. Put the mixture after ball milling into a vacuum oven at 120°C for 12 hours to obtain a lithium nickel manganese oxide precursor.

[0034] Step 2: Place the precursor in a folded conductive substrate and calcine the precursor under air atmosphere, pre-calcining at 500°C for 2 minutes, formal calcining at 850°C for 6 minutes, and annealing at 600°C for 2 minutes. The current is set as follows: pre-calcination process current 26A, formal calcination process current 44A, annealing process current 27.5A. Example

[0035] Step 1: Weigh Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and put them into a ball mill, then add a certain amount of anhydrous ethanol for wet grinding, and ball mill at a speed of 400 rpm for 4 hours. Put the mixture after ball milling into a vacuum oven at 120°C for 12 hours to obtain a lithium nickel manganese oxide precursor.

[0036] Step 2: Place the precursor in a folded conductive substrate and calcine the precursor under air atmosphere, pre-calcining at 500°C for 2 minutes, formal calcining at 850°C for 8 minutes, and annealing at 600°C for 2 minutes. The current is set as follows: pre-calcination process current 26A, formal calcination process current 44A, annealing process current 27.5A.

[0037] As mentioned above, too little or too much oxygen vacancies are not conducive to electrochemical performance, so it is necessary to accurately control oxygen vacancies. However, the traditional method has a long preparation cycle and high cost, and the method of controlling the internal defects of the material is also inefficient. This patent changes the preparation and control method and adopts fast Joule heating technology. Compared with the traditional method, the Joule heating method greatly shortens the calcination time, saves costs and improves efficiency. In obtaining a good crystallized sample ( Figure 1 ) At the same time, due to the short calcination time and heating and cooling time of the Joule heat method ( Figure 2 ), the diffusion time of atoms is short and the growth of crystal nuclei is inhibited, such as Figure 3It can be seen that compared with the material particles prepared by traditional methods with a basic size of 500nm-1.5um, the material particles prepared by Joule heat are smaller, most of which are between 100nm-500nm, and the oxygen atoms that escape during the calcination process do not have enough time to return to the lattice, resulting in more oxygen defects in the materials prepared by Joule heat. The effects of annealing process and changing calcination temperature and duration on the materials when using the Joule heat method are further explored. For example, through the analysis of the results of the examples, the only difference between Example 1 and Example 3 is whether there is an annealing process. Example 1 has no annealing process, and the crystallinity is relatively poor at this time. This is because the rapid cooling prevents the molecules from arranging in an orderly manner in time, resulting in too many amorphous areas and too disordered structures. After the annealing process is added to Example 3, the crystallinity is improved, indicating that appropriate annealing treatment will help the molecules in the material to rearrange and order, improve the crystallinity of the material, and make the structure more stable. In Examples 2, 3, and 4, the other parameters were fixed and only the calcination temperature was increased. In Examples 3, 5, and 6, the other parameters were fixed and only the calcination time was extended. As the temperature increased or the calcination time was longer, more energy was applied to the material, more oxygen was released during the calcination process, and more oxygen vacancies were generated in the material. The above materials were used as the positive electrode of the battery to assemble the battery and test it. As the oxygen vacancies increased, the electrochemical performance showed a hillside change (bad-good-bad), for example Figure 4 XPS data show that the material prepared by the traditional method has the least oxygen vacancies, followed by the materials with calcination time of 4min, 6min, and 8min. Figure 5 The battery cycle performance of several samples was demonstrated, among which the JTS-LNMO-4min sample with a moderate number of oxygen vacancies had the best cycle performance. After 500 cycles at 1C current, the reversible capacity was still 106.5mAh / g, and the capacity retention rate was as high as 90.8%. It could still maintain a capacity of 75mAh / g at 5C rate. The second sample with the second most oxygen vacancies, the JTS-LNMO-6min sample, had a capacity retention rate of 78.2% at 1C and a capacity of 64mAh / g at 5C rate. The traditional sample with the least number of oxygen vacancies had a capacity retention rate of 69% at 1C and a capacity of 60mAh / g at 5C rate. The worst cycle stability was the JTS-LNMO-8min sample with the most oxygen vacancies, with a capacity retention rate of only 58.6% at 1C and a capacity of only 44mAh / g at 5C rate. It can be seen that the rapid Joule heating method can not only achieve LiNi 0.5 Mn 1.5 Rapid preparation of O4 materials and rapid regulation of oxygen vacancies can also be achieved to obtain LiNi with optimal electrochemical performance 0.5 Mn 1.5 O4 sample.

[0038] The above embodiments are only a part of several embodiments in actual research by the applicant of the present invention, and are only some embodiments cited for exemplary description of the present invention. The protection content of the invention is not limited to the above embodiments. Any modification, equivalent replacement or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock, characterized in that: The steps include: Step 1: preparing a lithium nickel manganese oxide precursor; Step 2: obtaining a conductive substrate, and using the conductive substrate to sandwich the lithium nickel manganese oxide precursor to fully transfer heat to the lithium nickel manganese oxide precursor; two conductive and heat conductive components are respectively connected to both ends of the conductive substrate; Obtaining a power source, and connecting the two poles of the power source to the two conductive and thermal conductive components respectively, and applying power according to a preset power-on time and heating temperature. After the conductive substrate is energized, it generates heat to heat the lithium nickel manganese oxide precursor to obtain a lithium nickel manganese oxide positive electrode material; The heating temperature is adjusted by adjusting the voltage and current output by the power supply, and the heating time is adjusted by adjusting the preset power-on time; The power-on process is performed according to the preset power-on time and heating temperature, and specifically includes a pre-calcination process, a formal calcination process and an annealing process in sequence.

2. The method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock according to claim 1, characterized in that: The step 1 specifically includes the following steps: weighing Li2CO3, NiO, and MnO2 in a stoichiometric ratio of 0.55:0.5:1.5 and putting them into a ball mill, then wet-milling them at a speed of 400 rpm for 4 hours, and baking the mixture after ball milling in a vacuum oven at 120° C. for 12 hours to obtain a lithium nickel manganese oxide precursor.

3. The method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock according to claim 1, characterized in that: In step 2, the power-on time of the pre-calcination process is 2 minutes and the temperature is 500°C; the power-on time of the formal calcination process is 4-8 minutes and the temperature is 800-900°C; the power-on time of the annealing process is 0-2 minutes and the temperature is 600°C.

4. The method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock according to claim 1, characterized in that: In the step 2, the conductive substrate sandwiches the lithium nickel manganese oxide precursor, which specifically includes the following steps: folding the conductive substrate in half, sandwiching the lithium nickel manganese oxide precursor between the folded conductive substrates; Each of the conductive and heat-conducting components comprises two brass clamping parts, which are used to clamp the two ends of the folded conductive substrate respectively, so that the conductive substrate is in full contact with the brass clamping parts to reduce contact resistance and conduct heat quickly.

5. The method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock according to claim 2, characterized in that: In step 1, the raw material Li2CO3 is in excess of 10%.

6. The method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock according to claim 1, characterized in that: In the step 2, the conductive substrate includes any one of the following materials: stainless steel foil, iron foil, tungsten boat, carbon cloth, carbon paper, and graphite material.

7. The method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock according to claim 4, characterized in that: The method of sandwiching the lithium nickel manganese oxide precursor between the folded conductive substrates specifically includes: the two ends of the folded conductive substrate are clamped to form a groove, the precursor is placed therein and evenly spread out, so that the precursor is in close and full contact with the conductive substrate, the precursor is evenly heated, and the heat is quickly conducted.

8. The method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock according to claim 1, characterized in that: The power supply in step 2 includes any one of a direct current power supply and an alternating current power supply, and the direct current power supply includes a constant current power supply and a constant voltage power supply.

9. The method for synthesizing a positive electrode material of lithium nickel manganese oxide by rapid Joule thermal shock according to claim 1, characterized in that: The lithium nickel manganese oxide positive electrode material is in a granular form, and the particle size of the particles is between 100nm and 500nm.

10. The method for synthesizing lithium nickel manganese oxide positive electrode material by rapid Joule thermal shock according to claim 9, characterized in that: The following steps are also included: The lithium nickel manganese oxide positive electrode material is used as a battery positive electrode to assemble a battery, and the number of oxygen vacancies is adjusted by adjusting the heating temperature and time of the formal calcination process, thereby adjusting the battery cycle performance; Set the pre-calcination temperature to 500°C and the heating time to 2 min; the annealing temperature to 600°C and the heating time to 2 min; When the formal calcination temperature is 850℃ and the heating time is 4min, the reversible capacity of the battery is still 106.5mAh / g after 500 cycles, and the capacity retention rate reaches 90.8%. It can still maintain a capacity of 75mAh / g at a 5C rate.

Citation Information

Patent Citations

  • Preparation method of carbon and lanthanum oxide co-coated modified lithium nickel manganate positive electrode material

    CN110563052A

  • High-voltage lithium nickel manganese oxide cathode material and preparation method thereof

    CN111769286A

  • Battery positive electrode material and method for rapidly synthesizing battery positive electrode material

    CN113247962A

  • Rapid preparation method and application of lithium manganate positive electrode material

    CN113353986A

  • Preparation method for synthesizing lithium-rich manganese-based positive electrode material by short-time rapid thermal shock method and application of lithium-rich manganese-based positive electrode material

    CN113511692A

Cited By

  • Preparation method of nickel-copper-doped lithium manganate positive electrode material and nickel-copper-doped lithium manganate positive electrode material

    CN120646923A

  • Method for rapid Joule thermal synthesis of YFeO3 ferrite material and application of YFeO3 ferrite material

    CN120864874A

  • Positive electrode active material and preparation method thereof

    CN121331814A